Structural and functional changes in the mucous membrane of the stomach and duodenum in miners of Kryvbas, who suffer from chronic gastroduodenitis (clinical and morphological study). - Vasilenko, A. M.; Burtniak, T. Z. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Clinical and experimental observations of many authors indicate the influence of industrial and professional factors of mining enterprises on the occurrence, the nature of the course of diseases of the stomach and duodenum. Objective. The aim of the work was to study the morphological and functional changes in the mucous membrane of the stomach and duodenum in the miners of Kryvbas, who suffer from chronic gastroduodenitis, to isolate the main diagnostic signs of the disease. Methods. 145 workers of Krivbass industrial enterprises suffering from chronic gastroduodenitis were examined. Male patients aged 30 to 60 years, work experience is more than 10 years. The first group includes 102 miners having professional insalubrity, the second group comprised 43 patients with chronic gastroduodenitis who do not have contact with occupational insalubrity. Results. Morphological studies have shown that with chronic gastroduodenitis inflammatory and atrophic changes in most patients predominate in one of the two organs involved in the pathological process - in the stomach or duodenum. Thus, in the ulcerative form of chronic gastroduodenitis, the mucosa of the duodenum is more deeply affected, with a possible disruption of its neurohumoral function, and in case of a gastritis-like form, deeper lesions are observed in the gastric mucosa. A direct correlation was established between the length of service, the duration of the disease, and the prevalence of inflammatory-atrophic changes in the gastroduodenal zone. Conclusion. With chronic gastroduodenitis, deeper lesions of the mucous membrane of the stomach and duodenum are observed compared with patients who do not have no contact with occupational insalubrity. At miners, inflammatory and atrophic changes are more pronounced in the mucosa of the duodenum than in the stomach, which causes a higher incidence of ulcerative form of chronic gastroduodenitis.